Saat Anak Merancang Ruangannya Sendiri - Andi Karina Deapati; Ria Wikantari; Mohammad Mochsen Sir; Abdul Mufti Radja; Afifah Harisah; Syahriana Syam (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
Almost all buildings worldwide are designed by adults, while end-users can come from a wide age range, including kids. This activity was carried out at the Impian Elementary School, aiming to describe the design process in the classroom at the school involving kids and to analyze the changes in the design result so that we could see their expectations for their dream classroom. The kids' participation in the design process requires an understanding that children should not be seen as passive users in the room they can be seen as agents who can develop design ideas and produce dynamic changes for their environment. The method is a participatory method involving kids in the design process, and adults as companions. The students from grades 4 to 6 which consisted of 25 kids were divided into 4 groups to take part in a design workshop by developing creative ideas about the classroom through the creation of three-dimensional models. A simple pre-test was carried out to find out the expectations of their classrooms, then compared with the results of their design execution at the end of the activity. The four models produced from the four groups have different spatial arrangements, colors, and decorations from one. The four models of classrooms have something in common, they are colorful with large whiteboards and some wall decorations that are much different from their current classrooms situation. We consider this conclusion for the school to rearrange their classrooms.